Maya 4.5 Savvy - Kundert-Gibbs, John (Sybex, 2011)
Maya is famed for its intuitive interface, and yet this high-end 3D application is so powerful that no one masters it without help. Maya 4.5 Savvy is an update to the successful Mastering Maya 3 and provides precisely the help you need to take your skills to the next level, regardless of your field and how much or little you already know. Maya 4.5 Savvy is the first of Sybex's authorized, Alias|Wavefront Approved titles.